2014
DOI: 10.3389/fenvs.2014.00022
|View full text |Cite
|
Sign up to set email alerts
|

Biological reduction of iron to the elemental state from ochre deposits of Skelton Beck in Northeast England

Abstract: Ochre, consequence of acid mine drainage (AMD), is iron oxides-rich soil pigments that can be found in the water drainage from historic base metal and coal mines. The anaerobic strains of Geobacter sulfurreducens and Shewanella denitrificans were used for the microbial reduction of iron from samples of ochre collected from Skelton Beck (Saltburn Orange River, NZ 66738 21588) in Northeast England. The aim of the research was to determine the ability of the two anaerobic bacteria to reduce the iron present in oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The conventional processes are complex due to the different intensive sub-processes and use of large amounts of chemicals and generation of toxic sludges. [13,42,43] Carbothermal reduction of Cr(VI) was conducted by adding carbon at temperature ranging from 1000 to 1400 o C in a TGA apparatus with particle size limitation of the Cr(VI) contaminated soil sample [27]. To achieve a complete reduction 15% carbon was added to soil, however, evaluation of CO2 emission was ignored during the process.…”
Section: Comparison Of Conventional and Bioremediation Methodsmentioning
confidence: 99%
“…The conventional processes are complex due to the different intensive sub-processes and use of large amounts of chemicals and generation of toxic sludges. [13,42,43] Carbothermal reduction of Cr(VI) was conducted by adding carbon at temperature ranging from 1000 to 1400 o C in a TGA apparatus with particle size limitation of the Cr(VI) contaminated soil sample [27]. To achieve a complete reduction 15% carbon was added to soil, however, evaluation of CO2 emission was ignored during the process.…”
Section: Comparison Of Conventional and Bioremediation Methodsmentioning
confidence: 99%
“…The reverse processthat is, the reduction of oxidized iron to ZVIhas also been observed in some abiotic reactions. One example is the formation of Fe(0) in awaruite, a nickel and iron-containing alloy, in serpentinizing environments . Several studies have also reported the reduction of Fe­(III) in aqueous tea-leaf extracts to ZVI. However, to the best of our knowledge, only one study reported the presence of small X-ray diffraction peaks of Fe(0) in microbial enrichment cultures of Geobacter sulfurreducens and Shewanella denitrificans that grew on ochre pigment …”
Section: Introductionmentioning
confidence: 95%
“…Several studies have also reported the reduction of Fe(III) in aqueous tea-leaf extracts to ZVI [32][33][34]. However, to the best of our knowledge, only one study reported the presence of small X-ray diffraction peaks of Fe(0) in microbial enrichment cultures of Geobacter sulfurreducens and Shewanella denitrificans that grew on ochre pigment [35].…”
Section: Introductionmentioning
confidence: 97%
“…Heavy metal pollution is caused as a result of both natural and anthropomorphic activities like mining, smelting, industrial production, using of metals, and metal containing compounds for domestic and agricultural applications. These sources were reported to contribute to human exposure and environmental contamination by various researchers (Herawati et al, 2000;Goyer, 2001;Zouboulis et al, 2004;He et al, 2005;Rahman and Bastola, 2014). The potential sources of environmental contaminations are shown in Figure 1.…”
Section: Metals As Environmental Pollutantsmentioning
confidence: 96%
“…This process of chemical-biological integrated treatment is considered to be a highly economical and eco-friendly alternative to treat heavy metals containing wastewater. Implementation of this integrated treatment than the individual chemical or biological treatment has been reported to be advantageous and has shown significant results of heavy metal removal by many researchers worldwide (Rahman and Murthy, 2005;Abdulla et al, 2010;Rahman and Bastola, 2014;Greenwell et al, 2016;Mao et al, 2016;Pradhan et al, 2017). When implied alone, both the treatments face, their merits, and demerits.…”
Section: Chemical-biological Remediation Approachmentioning
confidence: 99%